Autoimmune hepatitis following Epstein-Barr virus infection: a diagnostic dilemma. Issue 7 (10th July 2019) - Peng, Haoran; Lim, Tanna; Nam, Jae; Lee, Jin
Abstract : Epstein-Barr virus (EBV) infections frequently affect the liver and cause hepatitis. EBV is a well-known trigger of certain autoimmune diseases. There are few case reports showing the evidence of autoimmune hepatitis (AIH) following EBV infection. However, the diagnosis of AIH is very challenging in the setting of an acute infection. Here, we demonstrate a case of AIH following EBV infection in a patient ultimately recovered after receiving treatment for AIH.